There Was a Black Hole That Swallowed the Universe - Ferrie, Chris; Batori, Susan (Naperville, Illinois : Sourcebooks Explore, 2019)
"From the #1 bestselling science author for kids comes a hilarious new take on the universe and everything in it. Using the familiar rhythm of "There Was an Old Lady Who Swallowed a Fly," follow along as the black hole swallows up everything that exists, from the biggest to the smallest pieces of matter. The silly, vibrant artwork is sure to make stargazers of all ages smile. Included in the book will be instructions for revealing secret, invisible text and artwork that reverses the story from nothing to the scientific creation of everything!"--
Keywords: Outer space -- Juvenile literature; Universe -- Juvenile literature; Outer space; Universe